2017
DOI: 10.3174/ajnr.a5375
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Incomplete Occlusion following Pipeline Embolization of Intracranial Aneurysms: Is It Less Effective in Older Patients?

Abstract: Complete occlusion following PED treatment of intracranial aneurysms can be influenced by several factors related to the patient, aneurysm, and treatment. Of these factors, older age (older than 70 years) and nonsmoking status were independent predictors of incomplete occlusion. While the physiologic explanation for these findings remains unknown, identification of factors predictive of incomplete aneurysm occlusion following PED placement can assist in patient selection and counseling and might provide insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 35 publications
4
49
0
1
Order By: Relevance
“…20,21 Adeeb et al found that age >70 years and nonsmoking status independently predicted incomplete occlusion, and suggested lower occlusion rates in the elderly may be related to a deficiency in the endothelial repair pathway, with incomplete endothelization of the stent. 22 Our results corroborate these predictive findings with age, history of SAH, >6 months dual antiplatelet therapy post-PED implant, aneurysm maximal diameter, and fusiform morphology being associated with incomplete occlusion.…”
Section: Factors Associated With Aneurysm Occlusionsupporting
confidence: 87%
“…20,21 Adeeb et al found that age >70 years and nonsmoking status independently predicted incomplete occlusion, and suggested lower occlusion rates in the elderly may be related to a deficiency in the endothelial repair pathway, with incomplete endothelization of the stent. 22 Our results corroborate these predictive findings with age, history of SAH, >6 months dual antiplatelet therapy post-PED implant, aneurysm maximal diameter, and fusiform morphology being associated with incomplete occlusion.…”
Section: Factors Associated With Aneurysm Occlusionsupporting
confidence: 87%
“…The notion that aneurysm size is an important predictor of aneurysm occlusion is also supported by a large multicenter retrospective study of 380 aneurysms treated with Pipeline embolization. 18 In that study, the median aneurysm diameter was 7.7 mm, comparable with that in EuFRED, and the complete occlusion rate in aneurysms followed for at least 1 year was 83.9%. The study also included 13.4% of aneurysms located in the posterior circulation.…”
Section: Aneurysm Occlusion After Fredmentioning
confidence: 61%
“…Assessing factors related to aneurysm occlusion, we found that patients younger than 60 years of age had a higher occlusion rate compared with the older group (90% versus 76%, P Ï­ .01). Adeeb et al, 37 after treatment of 465 intracranial aneurysms with PEDs, showed that older age was a significant predictor of incomplete occlusion at last follow-up. Although the exact reasons are currently unknown, the lower occlusion rates in the elderly may be related to a deficiency in the endothelial repair pathway, with incomplete endothelization of the stent.…”
Section: Angiographic Outcomesmentioning
confidence: 99%
“…Although the exact reasons are currently unknown, the lower occlusion rates in the elderly may be related to a deficiency in the endothelial repair pathway, with incomplete endothelization of the stent. 37…”
Section: Angiographic Outcomesmentioning
confidence: 99%